Digital library for geography examination resources. - Chua, Lian Heong. (2008)
This project describes the development of a Web-based digital library application containing past-year geography examination questions, solutions and supplementary resources to assist students in their preparation for the Singapore-Cambridge GCE ‘O’ level examination in geography. It provides an interactive, non-sequential approach to learning that supplements textbooks.